Distribution, diversity gradients and Rapoport's elevational rule in the black scavenger flies of the Swiss Alps (Diptera: Sepsidae). Issue 4 (9th February 2015) - Rohner, Patrick T.; Bächli, Gerhard; Pollini Paltrinieri, Lucia; Duelli, Peter; Obrist, Martin K.; Jochmann, Ralf; Blanckenhorn, Wolf U.; Basset, Yves; Gilbert, Francis
Abstract Elevational gradients influence the distribution and abundance of species drastically and can lead to variation in community composition. Although coprophagous flies are of ecological and economic importance, their biodiversity and distribution are largely neglected. We studied the impact of steep elevational gradients and geography on the distribution of sepsid flies in the Swiss Alps. Sepsidae are a family of acalyptrate flies strongly associated with decaying organic matter and vertebrate dung, and characterised by a high extent of sympatry in their breeding substrates. Historical, haphazardly sampled specimens from 116 locations covering an elevational range from 200 to 2000 m were available in ethanol collections of various Swiss museums. Nineteen species encompassing all native genera (Meroplius, Nemopoda, Saltella, Sepsis and Themira) were recorded. Local species richness increased linearly with elevation, while area‐corrected regional species richness of elevational belts increased asymptotically. Species occurring at higher altitudes had lower wing loadings and greater elevational ranges than lowland species, supporting Rapoport's elevational rule. Despite compositional similarities, the sepsid communities of the northern lowlands differed significantly from the alpine sepsid fauna. The southern lowlands were particularly differentiated in community composition due to a number of presumably thermophilic species that predominantly occur south of the Alps. Relative abundances of several species were thus strongly affected by elevation and climatic variables. We illustrate the impact of elevational gradients and geography on a community of closely related, often sympatric species, and discuss potential mechanisms of niche partitioning via temporal succession, thermal adaptation and differential resource use.